The Incidence of Neuropathy Following Upper Extremity Nerve Blocks. Issue 1 (January 1985) - Wolfe, Robert; Winchell, Sidney W.
Abstract : This study was undertaken to determine the incidence of neuropathy following upper extremity nerve blocks when these blocks were administered by a group of private-practicing and experienced anesthesiologists. The block history of 854 consecutive patients was recorded and an overall incidence of post-block neuropathy of 0.36% was found, ( i.e., three patients out of 854). The numbers were felt to be too small to draw a valid conclusion as to etiology. We concluded that the incidence of post-block neuritis is relatively low and the severity of the neuropathy is not great. Studies purporting to demonstrate significant differences in incidence of neuropathy related to technique or drugs must be based on very large populations. No such studies are currently in the literature.